1992
DOI: 10.1104/pp.100.4.1670
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution and Characterization of a Calmodulin-Stimulated Ca2+-Pumping ATPase Purified from Brassica oleracea L.

Abstract: Purification and functional reconstitution of a calmodulin-stimulated Ca2"-ATPase from cauliflower (Brassica oleracea L.) is described. Activity was purified about 120-fold from a microsomal fraction using calmodulin-affinity chromatography. The purified fraction showed a polypeptide at 115 kD, which formed a phosphorylated intermediate in the presence of Ca2 , together with a few polypeptides with lower molecular masses that were not phosphorylated. The ATPase was reconstituted into liposomes by 3-([cholamido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
1

Year Published

1993
1993
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 36 publications
4
35
1
Order By: Relevance
“…Second, a synthetic peptide corresponding to this region bound strongly to CaM. Whereas binding of the native enzyme to CaM is strictly dependent on Ca2+ [6], the synthetic peptide bound to CaM in both the presence and absence of Ca2+ (Fig. 4A).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Second, a synthetic peptide corresponding to this region bound strongly to CaM. Whereas binding of the native enzyme to CaM is strictly dependent on Ca2+ [6], the synthetic peptide bound to CaM in both the presence and absence of Ca2+ (Fig. 4A).…”
Section: Discussionmentioning
confidence: 94%
“…The properties of the purified enzyme have been described [5,6]. Trypsin digestion and sequencing of the resulting peptides were carried out by Bo Ek, Uppsala Genetic Center, Swedish University of Agricultural Sciences.…”
Section: Affinity Purification Of Vacuolar Ca 2 + -Atpase and Sequencmentioning
confidence: 99%
“…In contrast, CaM-stimulated Ca2+-ATPases in plants have been reported to be present in the ER (Hsieh et al, 1991;Askerlund and Evans, 1992;Gilroy and Jones, 1993;Liss and Weiler, 1994;Logan and Venis, 1995), the vacuolar membrane (Gavin et al, 1993), and the chloroplast envelope (Nguyen and Siegenthaler, 1985), as well as the plasma membrane (Robinson et al, 1988;Rasi-Caldogno et al, 1993, 1995 Olbe and M. Sommarin, unpublished data; for a review, see Askerlund and Sommarin, 1996). CaM-stimulated Ca2+-ATPase in cauliflower (Brassica olevacea L.) was earlier found to be located mainly in a low-density intracellular membrane fraction that was suggested to be the ER, but also in the plasma membrane (Askerlund and Evans, 1992). More recent investigations have shown that the distribution of the intracellular CaM-stimulated Ca2+-ATPase in cauliflower correlates much better with vacuolar membrane markers than with ER markers, suggesting that it may be located in the vacuolar membrane (P. Askerlund, unpublished data).…”
mentioning
confidence: 99%
“…So far only a few CaM-stimulated Ca2+-ATPases (of 120 and 111-115 kD) have been purified from low-density endomembranes of plants (this work; Askerlund and Evans, 1992;Askerlund, 1996); however, numerous reports of CaM-stimulated Ca2+ transport in endomembranes (Brauer et al, 1990;Hsieh at al., 1991;Gilroy and Jones, 1993;Bush and Wang, 1995) illustrate that this is a common feature in plants. Recent studies in corn roots have attributed a low-density, CaM-stimulated Ca2+ pump to the vacuole alone (Gavin et al, 1993;Pfeiffer and Hager, 1993); however, in the tendrils of Bryonia, CaMstimulated Ca'+ transport was found in purified ER after ribosomes had been stripped (Liss and Weiler, 1994).…”
Section: Role Of a Cam-stimulated 120-kd Ca2+ Pump In Endomembranesmentioning
confidence: 95%
“…The animal ER-type Ca2' pump is distinguished from the animal PM-type Ca2+ pump by its sensitivity to thapsigargin or cyclopiazonic acid, and by its insensitivity to CaM (Schatzmann, 1989;Siedler et al, 1989;Carafoli 1992); however, the results from plants are more ambiguous. For example, Ca2+ pump activity in the ER fraction is insensitive to CaM in wheat aleurone layers (Bush and Wang, 1995) and in garden cress (Buckhout, 1984), yet other studies show high CaM-stimulated Ca2+ transport in endomembranes, including the ER from carrot (Daucus carota) suspension cells (Hsieh et al, 1991), cauliflower florets (Askerlund and Evans, 1992), corn roots (Brauer et al, 1990), and tendrils (Liss and Weiler, 1994).…”
mentioning
confidence: 99%